Estimación del ahorro energético por utilización de tecnologías más eficientes y alternativas de energía eléctrica en pymes turísticas del cantón Junín - Carrera Mendoza, María Marcela (2019)
The purpose of this research project is to estimate energy savings by using more efficient and alternative electric energy technologies in Tourist SMEs in Canton Junín. It is a quantitative and qualitative research, as well as exploratory because it is the first investigation of its kind that is carried out in the object of practical study. In order to fulfill the objectives, four stages were worked on: Analysis of the consumption of electrical energy in tourist SMEs, identification of more efficient technologies and alternatives of electrical energy in relation to those currently employed, estimation of the saving of electrical energy by the implementation of technologies more efficient or alternative and design of an energy saving action plan using more efficient and alternative electric energy technologies. Among the techniques and tools used were field research, analysis and synthesis of information, observation, bibliographic analysis and use of Microsoft Excel and STATGRAPHICS Centurion. Among the main results are: an analysis of the consumption of electricity with an increasing trend in 14 of the 17 tourist SMEs studied; a seasonal behavior of electric power consumption for nine of the SMEs studied, with the month with the lowest demand for electric power consumption in December, and the highest demand consumption without a frequency of occurrence concentrated in a specific month; an inventory of a representative sample of three tourist SMEs of the Junín canton in which savings opportunities were evidenced mainly in the areas of lighting, household appliances and air conditioning; the estimation of the consumption of electric energy by implantation of more efficient and alternative technologies of the tourist SMEs considered in the sample, determining that the estimated saving by substitution to alternative technology (solar) is superior to the estimated saving of electrical energy with substitution by more technologies Efficient in the three SMEs studied.